2019
DOI: 10.1093/femsec/fiz208
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhiza has little influence on N2O potential emissions compared to plant diversity in experimental plant communities

Abstract: Denitrification is an ecosystem process linked to ongoing climate change, because it releases nitrous oxide (N2O) into the atmosphere. To date, the literature covers mostly how aboveground (i.e. plant community structure) and belowground (i.e. plant-associated soil microbes) biota separately influence denitrification in isolation of each other. We here present a mesocosm experiment where we combine a manipulation of belowground biota (i.e. addition of Rhizophagus irregularis propagules to the indigenous mycorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…26,27 Yet, only a few studies have investigated the effects of plant roots and their associated AMF on soil N 2 O emission, and these have yielded variable results. 21,25,28,29 Using either AMF-deficient tomato mutants or soil sterilization to manipulate the presence of AMF, for example, Bender et al 21 showed that AMF significantly reduced soil N 2 O emission. Other studies, however, showed or suggested that root exudates and labile C from plant roots and AMF may enhance denitrifiers and thus increase soil N 2 O production.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Yet, only a few studies have investigated the effects of plant roots and their associated AMF on soil N 2 O emission, and these have yielded variable results. 21,25,28,29 Using either AMF-deficient tomato mutants or soil sterilization to manipulate the presence of AMF, for example, Bender et al 21 showed that AMF significantly reduced soil N 2 O emission. Other studies, however, showed or suggested that root exudates and labile C from plant roots and AMF may enhance denitrifiers and thus increase soil N 2 O production.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Plant roots and their associated microbes, especially arbuscular mycorrhizal fungi (AMF), compete against nitrifiers and denitrifiers for N substrates and likely suppress N 2 O emission. ,, AMF form symbiotic associations with roots of over 80% plant species, in which AMF obtain soil nutrients in exchange of photosynthates from host plants. , Yet, only a few studies have investigated the effects of plant roots and their associated AMF on soil N 2 O emission, and these have yielded variable results. ,,, Using either AMF-deficient tomato mutants or soil sterilization to manipulate the presence of AMF, for example, Bender et al showed that AMF significantly reduced soil N 2 O emission. Other studies, however, showed or suggested that root exudates and labile C from plant roots and AMF may enhance denitrifiers and thus increase soil N 2 O production. , Because of their extensive mycelial network, changes in C and N inputs induced by AM fungi can also significantly affect the composition and activities of the microbial community in the mycorhizosphere. Qiu et al showed that under elevated atmospheric CO 2 , plant roots with AMF reduced nir K abundance and the ( nir K + nir S)/ nos Z ratio, although AMF alone had no significant effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of AMF on soil N 2 O emission are unclear. Some studies found that AMF had little effect on N 2 O emission [10] or increased N 2 O emission [11], while others reported that AMF symbiotic activities could reduce N substrate for N 2 O production by increasing plant N uptake [12,13]. One of the major reasons for these mixed results might be the different AMF species or mycorrhiza-defective mutant used in their experiments [10,11,14].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found that AMF had little effect on N 2 O emission [10] or increased N 2 O emission [11], while others reported that AMF symbiotic activities could reduce N substrate for N 2 O production by increasing plant N uptake [12,13]. One of the major reasons for these mixed results might be the different AMF species or mycorrhiza-defective mutant used in their experiments [10,11,14]. Based on the morphological characteristics of spores, 244 different AMF species have been described [15], and direct sequencing of fungal ribosomal RNA genes from the soil has revealed the existence of 341 virtual AMF taxa so far [16,17].…”
Section: Introductionmentioning
confidence: 99%